Rheological Model for Generalized Energy and Mass Transfer through Hybrid Nanofluid Flow Comprised of Magnetized Cobalt Ferrite Nanoparticles - Al-Mubaddel, Fahad S.; Allehiany, F. M.; Nofal, Taher A.; Alam, Mohammad Mahtab; Ali, Aatif; Asamoah, Joshua Kiddy K. (Hindawi, 2024)
This article is published by Hindawi 2022 and is also available at https://doi.org/10.1155/2022/7120982